2005
DOI: 10.1007/s11136-004-0794-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life related to type 1 Gaucher disease: Spanish experience

Abstract: Physical activities and bone disease grade 1 and 3 are negatively related to QOL. Nevertheless no correlation was found with bone pain crisis, possibly due to the transitory character of this event. In spite of the improvement induced by ERT, a quarter of patients remained with physical limitations related to bone disease as well as in need of orthopaedic correction of bone sequelae. In order to improve the QOL an accurate evaluation of bone disease to define therapeutic approaches must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 8 publications
2
57
1
1
Order By: Relevance
“…For patients with GD receiving ERT, six studies were retrieved (Damiano et al 1998;Masek et al 1999;Giraldo et al 2000Giraldo et al , 2005Pastores et al 2003;Weinreb et al 2007). The study conducted by Masek et al (1999) with North American patients with GD was used for comparisons with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with GD receiving ERT, six studies were retrieved (Damiano et al 1998;Masek et al 1999;Giraldo et al 2000Giraldo et al , 2005Pastores et al 2003;Weinreb et al 2007). The study conducted by Masek et al (1999) with North American patients with GD was used for comparisons with our study.…”
Section: Discussionmentioning
confidence: 99%
“…ERT is currently available for the following LSDs: GD, FD, MPS I, MPS II, MPS VI, and Pompe disease. The effects of ERT on the QoL of patients with GD have already been described (Damiano et al 1998;Masek et al 1999;Giraldo et al 2000;Pastores et al 2003;Giraldo et al 2005;Weinreb et al 2007), but are still unknown for patients with FD.…”
Section: Introductionmentioning
confidence: 92%
“…Compared to the visceral and the hematological disease, bone involvement in patients with GD1 causes the greatest impairment in the quality of life. (6) The most impactful and dramatic clinical complications arising from bone involvement are AVN, osteopenia, and fractures. (2,5,7,8) These complications permanently alter the health status of affected patients due to chronic pain, disability, and the need for surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…(2,5,7,8) These complications permanently alter the health status of affected patients due to chronic pain, disability, and the need for surgical interventions. (6) The precise risk of AVN in untreated GD1 (not receiving imiglucerase therapy) was estimated to be 22.8 per 1000 person years (95% confidence interval [CI], 20.2-25.7) of follow-up. (9) Imiglucerase therapy reduces the incidence of AVN to 13.8 per 1000 years of followup.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain utility-based quality of life data, three separate methods are adopted: a literature review, mapping to EuroQol 5 Dimensions (EQ-5D) and estimation of public preference utilities. The literature review identified three studies that reported economic evaluations, 155,156 all of which produced very high ICERs despite optimistic assumptions being applied (lower prices than available in the UK and high estimates of effectiveness). Using cohort studies to assess the quality of life of an average patient with Gaucher's disease aged between 40 and 49 years, an increment to quality of life is estimated from treatment of ERT.…”
Section: Data Receivedmentioning
confidence: 99%